Thermomechanical Characterization of a Series of Crosslinked Poly[ethylene-co-(vinyl acetate)] (PEVA) Copolymers. Issue 1718 (2015) - Heuchel, Matthias; Al-Qaisi, Laith; Kratz, Karl; Nöchel, Ulrich; Behl, Marc; Lendlein, Andreas
ABSTRACT: Crosslinked poly[ethylene- co -(vinyl acetate)] (cPEVA) has been recently introduced as a polymer material, which can be functionalized with various shape-memory effects by solely altering the thermomechanical treatment called programming. In this study two series of cPEVAs with different vinyl acetate contents of 18 wt% (cPEVA18) and 28 wt% (cPEVA28) comprising different crosslink densities were investigated by differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) in the temperature range of -130 °C to 120 °C. DMTA tests were performed in torsion mode, because such movements are highly relevant in the context of complex shape changes in shape-memory polymer based devices. Finally, the obtained DMTA results were compared with DMTA conducted in tension mode. Swelling experiments revealed a gel content in the range from 81% to 90% for cPEVA18 samples while for cPEVA28s a complete conversion was observed. The degree of swelling was found to decrease substantially with increasing crosslink density for both cPEVA series. The influence of VA content and extent of crosslinking on the appearance of the respective melting ( T m ) and glass transition ( T g ) as well as the thermomechanical properties of cPEVA systems could be demonstrated by discussing both DSC and DMTA results. The temperature range of mechanical stability correlates with the VA content and is determined by decreasing T m values. The cross links do barely alter the stiffness of a PEVA up to the T m rang, but lead to constant mechanical rigidity in the rubbery range above T m .